Variation in Composition of Yeast Phosphohexosans - Slodki, M. E. (1970)
Omitting of KH(2)PO(4) from culture media leads to the production of altered phosphohexosans or neutral extracellular mannans by yeasts that otherwise elaborate phosphogalactans and phosphomannans.